Individual performance-based incentives for health care workers in Organisation for Economic Co-operation and Development member countries: a systematic literature review. Issue 6 (June 2022) - Lin, Tracy Kuo; Werner, Kalin; Witter, Sophie; Alluhidan, Mohammed; Alghaith, Taghred; Hamza, Mariam M.; Herbst, Christopher H.; Alazemi, Nahar
Highlights: This study reviews the evidence on effectiveness of individual-level PBI for health care. Nearly a third of included studies reported no change in outcomes. There is substantial heterogeneity in the structure of how PBI is delivered. Most PBIs in OECD countries relied on positive reinforcement mechanisms. Some may detract from areas of unincentivized care or deepen existing disparities. Abstract: In response to rising costs and growing concerns about safety, quality, equity and affordability of health care, many countries have now developed and deployed performance-based incentives, targeted at facilities as well as individuals. Evidence of the effect of these efforts has been mixed; it remains unclear how effective strategies of varying design and magnitude (relative to provider salary) are at incentivizing individual-level performance. This study reviews the current evidence on effectiveness of individual-level performance-based incentives for health care in Organisation for Economic Co-operation and Development countries, which are relatively well situated to implement, monitor and evaluate performance-based incentives programs. We delineate the conditions under which sanctions or rewards – in the context of gain-seeking, loss aversion, and increased social pressure to modify behaviors – may be more effective. We find that programs that utilized positive reinforcement methods are most commonly observed – with slightly more overall bonus incentives than payment per output or outcome achieved incentives. When comparing the outcomes from negative reinforcement methods with positive reinforcement methods, we found more evidence that positive reinforcement methods are effective at improving health care worker performance. Overall, just over half of the studies reported positive impacts, indicating the need for care in designing and adopting performance-based incentives programs.